Shear viscosity of strongly coupled N = 4 supersymmetric Yang-Mills plasma - Policastro, G; Son, D; Starinets, A (2001)
Conformal field theory was employed to compute the shear viscosity of strongly coupled supersymmetric Yang-Mills plasma. Relation of viscosity to the absorption cross-section of low-energy gravitons falling on a black brane was studied. The shear viscosity was found to be constant for a finite Hooft coupling limit.